Meropenem to Children With Febrile Neutropenia Induces Monoresistant Pseudomonas aeruginosa. Issue 8 (November 2020) - Mønster, Mette B.; Vissing, Nadja H.; Schrøder, Henrik; Grosen, Dorthe; Rosthøj, Steen; Frimodt-Møller, Niels; Wang, Mikala; Schønheyder, Henrik C.; Schmiegelow, Kjeld; Justesen, Ulrik S.; Nygaard, Ulrikka
Abstract : Antimicrobial resistance in Pseudomonas aeruginosa is a threat to children with cancer. We explored the association between P. aeruginosa resistance and previous antibiotic exposure. All children with cancer and P. aeruginosa bacteremia in 2007 to 2016 in Denmark, a country with an overall resistance rate of ∼3%, were included. Twenty percent (10/49) of isolates from children previously exposed to meropenem were meropenem nonsusceptible. The only significant risk factor of meropenem nonsusceptibility was previous meropenem therapy ( P =0.03). On the basis of these results, we suggest that meropenem should be reserved as a last resort for children with febrile neutropenia in countries with low antimicrobial resistance.